Study of the Dressed State of Hydrogen Atom in Electron Atom Elastic Collision in Laser Field - Yadav, K.; Gupta, S. P.; Nakarmi, J. J. (Journal of Nepal Physical Society, 2020)
We discuss the various important aspects of the theory of electron-atom elastic collision in laser field. We analyze the collision accompanied by the transfer of photons. We study the free electron states i.e. Volkov states and target atomic states i.e. Dressed states. We calculate the first-Born scattering matrix for electron-atom elastic collision. The present work accounts the calculation for hydrogen as target atom in soft photon limits i.e., in weak field. The dressing effect becomes significant in the region of low momentum transfer, reaches maximum of value of 25000 a.u. at momentum transfer of 0.44. This work explains that the differential cross-section does not occur very low and at very high momentum transfer. However, it occurs at moderate momentum transfer.